Fiscal Consolidations and Growth : Does Speed Matter? - Pennings, Steven (IMF Working Papers; Working Paper, 2013)
Should fiscal consolidations be front-loaded or proceed at a more steady pace, and how does this affect growth? We make an attempt to address this question using a three-step methodology. First, we modify a standard regression of growth on consolidation size to allow speed to affect the multiplier. Second, using the narrative dataset of Devries and others (2011), we construct a new sample of multi-year consolidation episodes for 17 advanced economies over 1978-2009. Third, we develop a novel concept of speed to measure the pace of the consolidation episodes identified in the data. The main empirical finding is that fast episodes have higher multipliers than gradual consolidations. This provides some preliminary support for consolidating at a steady pace, market access and a credible adjustment plan permitting. However, as the sample size is small, identifying mechanisms and testing robustness is difficult, and so our findings should not be interpreted causally.